2018
DOI: 10.3904/kjim.2016.108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with anxiety and depression in Korean patients with newly diagnosed advanced gastrointestinal cancer

Abstract: Background/AimsThe purpose of the present study was to assess the prevalence of and factors associated with anxiety and depression in Korean patients with advanced gastrointestinal cancer.MethodsOne hundred and twenty consecutive patients with newly diagnosed, advanced gastrointestinal cancer who were scheduled to receive palliative chemotherapy between July 2012 and June 2014 were enrolled in this observational prospective study. Anxiety and depression were assessed using the Hospital Anxiety and Depression S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
3
26
0
4
Order By: Relevance
“…In this study, the prevalence of anxiety among patients with diabetes, hypertension, and heart failure was 32% (95% CI: 27.3%-36.7%). This finding is consistent with the finding of studies conducted in Korea (30%) [16] and Brazil (33.7%) [17]. This is lower than the finding of a study conducted in three Asian countries (Cambodia, Myanmar, and Vietnam) (17%) [18].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the prevalence of anxiety among patients with diabetes, hypertension, and heart failure was 32% (95% CI: 27.3%-36.7%). This finding is consistent with the finding of studies conducted in Korea (30%) [16] and Brazil (33.7%) [17]. This is lower than the finding of a study conducted in three Asian countries (Cambodia, Myanmar, and Vietnam) (17%) [18].…”
Section: Discussionsupporting
confidence: 89%
“…No large longitudinal epidemiological studies assessing the humanistic burden of GC from diagnosis to death were identified in our search. Among the identified studies, five were systematic literature reviews [6367], nine were economic analyses [18, 20, 24, 26, 33, 37, 41, 42, 68], six were randomised controlled trials [6973], one was an observational study [74], seven were prospective cohort or case-control studies [39, 7580], seven were cross-sectional survey studies [8187], four were retrospective studies [8891] and one included a retrospective analysis and a prospective cross-sectional survey [92]. Only four studies used tools specific to GC or GEJC (GC module [STO22] and oesophago-gastric [OG25] modules of European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC-QLQ]) to assess HRQoL [78, 80, 86, 87].…”
Section: Resultsmentioning
confidence: 99%
“…CAG brings not only physical illness, but also several psychological distresses for patients. But most researchers often focus on psychology of gastric cancer patients (Chung et al., ; Nordin & Glimelius, ) and ignore the mental health of patients with CAG.…”
Section: Introductionmentioning
confidence: 99%